An approach for Supply Chain managing of small and big size business - Kundharu Saddhono; Joko Suyono; Susanti Susanti; Hartono Hartono; Anik Irawati; Mary Ismowati; Edi Pranyoto; Rianti Setyawasih (International Journal of Supply Chain Management, 2020)
Abstract— In every business there are requirements of the assets and resources. So, the supply chain managing links properly these areas to each other to make the efficiency. These resources can be financial, intangible and physical resources. If the resources are not available for the organization at the time when it require then it might be the reason for degrade of that business. The study of the relevant resources is very necessary, that take a role in the literature of business management. The intellectual capital is the aspect of impalpable assets, and its relational capacity promote the efficiency and profitability of the business. The intellectual capital known as the effort or work that a member put into the organization as intangible resources.  These resources include knowledge resources like copyright, patents, trademarks and other human’s ideas and experiments. So we can say that intellectual capital is the collection of all resources like relational capital, supply chain managing, structural and human, these are the resources that set the organizational competitive value.